Expansion of the Host Range of Xanthomonas euroxanthea First Occurrence in Sunflower in Bulgaria - Garcia, Eva (Plant disease, 2024)
Sunflower is a short-season crop of the Asteraceae family and the Helianthus genus and is the fourth most important oilseed crop in the world. During a field campaign, unusual symptoms (necrosis and longitudinal cracking of the petiole) were observed in a sunflower crop grown in the region of Kavarna (Dobrich district, Bulgaria) and strains of the genus Xanthomonas were isolated. Results based on phylogenetic and phylogenomic analyses showed that they clustered with Xanthomonas euroxanthea CPBF 424T species, a pathogenic strain isolated from walnut buds in Portugal and responsible for causing walnut bacterial blight (WBB). The sunflower strain showed five out of eight X. euroxanthea-specific markers (XEA4-XEA8), a pattern also observed in some strains isolated from Solanum lycopersicum, Phaseolus vulgaris and rainwater sources, reinforcing the emergence of a recent lineage-driven by evolutionary adaptations to new plant hosts. This is the first report of X. euroxanthea in sunflower crops in Bulgaria, which represents a potential threat to production and its distribution should be monitored